The effect of using mouthwashes to prevent bacteremia during initial therapy of periondontal treatment - Ihwigat, Mohamed Ahmed (My University, 2006)
Bakteriyemi kan dolaşımında bakterilerin varlığı anlamına gelir. Periodontal tedaviyi içeren dental işlemler yüksek risk grubundaki hastalarda ciddi enfeksiyonlar oluşturma potansiyeline sahiptir. Bu çalışmanın amacı başlangıç periodontal tedavi esnasında oluşan bakteriyeminin önlenmesinde Biotene ağız gargarasının etkinliğini değerlendirmek ve klorheksidin ile karşılaştırmaktır. Bu çalışmaya son üç ay içinde antibiyotik kullanmamış ve herhangi bir sistemik hastalığı olmayan 30 hasta dahil edildi. Çalışma, her bir grup 10 kişiden oluşmak kaydıyla 3 grup üzerinde yapıldı. Bunlar Biotene, %0.2 klorheksidin ve kontrol olarak ta serum fizyolojik grubu idi. Tüm deneklerden ultrasonik cihaz ile yapılan başlangıç periodontal tedavi esnasında 4 farklı zamanda kan örnekleri alındı. Sonra bu örnekler pour-plate methodu ve Signal Blood Culture System kullanılarak aerobik ve anaerobik olarak kültüre edildi. Biotene grubuna ait 4 hastada (%40), klorheksidin grubuna ait 3 hastada (%30) ve kontrol grubuna ait 5 hastada (%50) bakteriyemi tespit edildi. Bu çalışmanın sınırları dahilinde, bakteriyeminin önlenmesinde Biotene, klorheksidin kadar etkili bulunmuştur. Diğer yandan hem Biotene hem klorhexidin bakteriyeminin azaltılmasında kontrol grubundan daha etkilidir.

Bacteremia means the presence of viable bacteria in the circulating blood. Dental procedures including periodontal therapy may induce bacteremia with the potential to produce distant infections in high-risk patients. The aim of this study is to evaluate the effect of Biotene mouthwash on the incidence of bacteremia during initial periodontal therapy and to compare the efficacies of Biotene and chlorhexidine to find out if Biotene is as effective as chlorhexidine. This study included 30 chronic gingivitis patients with no medical history or antibiotic therapy within the previous 3 months. They were assigned to 3 groups; each group comprised 10 patients, Biotene group, 0.2% chlorhexidine gluconate group, and normal saline as a control group. Blood samples were taken at four different time points during ultrasonic scaling (US). Then, they were cultured aerobically and anaerobically by using Signal Blood Culture System and pour-plate methods. Bacteremia was detected in 4 patients of Biotene group (40%), in 3 patients of chlorhexidine group (30%), and in 5 patients of control group (50%). Within the limit of this study, Biotene is as effective as chlorhexidine in reducing the incidence of bacteremia since pre-procedural rinsing with Biotene and 0.2% chlorhexidine resulted in the same reduction in the incidence of bacteremia associated with US. On the other hand, they were both effective in reducing bacteremia and better than control group.
Keywords: Bakteriler; Diş Hastalıkları; Diş Hastalıkları_Tedavi